Bioactive polyethylene synthesized by ring opening metathesis polymerization for potential orthopaedic applications. Issue 15 (28th March 2023) - Guo, Jiayi; Park, Eun Ju; Teo, Yew Chin; Abbas, Asyraf; Goh, Denise; Smith, Raymond Alexander Alfred; Nie, Yuntong; Nguyen, Hang T. L.; Yeong, Joe Poh Sheng; Cool, Simon; Makio, Haruyuki; Teo, Peili
Abstract : Bioactive polyethylene incorporating hydrophobic PE-bearing macromonomers and hydrophilic PEGylated-peptide macromonomers was synthesized via ROMP. 3D-printed sheets of it with UHMWPE showed enhanced osteogenic activity for potential orthopaedic applications. Abstract : Efficient synthesis and bioevaluation of novel brush-type polyethylene-peptide copolymers for potential applications in orthopaedic implants are described here. The brush-type copolymers containing pendant arms of polyethylene (PE) and PEGylated biomolecules including linear arginyl-glycyl-aspartic acid (RGD) and collagen fragments (Gly-Pro-Hyp)3 were synthesized by ring-opening metathesis polymerization (ROMP) using the well-defined 2 nd generation Grubbs' ruthenium catalyst. The random copolymerization of two separate norbornene-dicarboxylic anhydride macromonomers allowed for the incorporation of hydrophilic PEGylated biomolecules into hydrophobic polyethylene. Thermal stability of this polyethylene-peptide copolymer was also markedly improved for melt extrusion-based material processing. The copolymers were blended with ultra-high molecular weight polyethylene (UHMWPE), extruded into filaments and 3D-printed into sheets using fused filament fabrication methods. The ability of these polyethylene materials to enhance osteogenic activity whilst reducing inflammatory response compared to pure UHMWPE was evaluated by the in vitro alkaline phosphatase (ALP) assay and an in vivo murine model study, respectively. The results presented here serves as a promising guide for biofunctionalization of polyethylene materials for potential orthopaedic applications.